Long-term results of monopolar versus bipolar radiofrequency ablation procedure for atrial fibrillation - SARAÇOĞLU, AYTEN (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2019)
Background: In this study, we aimed to evaluate the long-term outcomes of monopolar or bipolar radiofrequency ablation concomitant to mitral valve surgery in patients with atrial fibrillation. Methods: We retrospectively evaluated a total of 167 patients (67 males, 100 females; mean age 56.8 +/- 6.9 years; range, 48 to 65 years) with atrial fibrillation who underwent monopolar or bipolar radiofrequency ablation concomitant to mitral valve surgery between September 2001 and January 2015. The patients were divided into two groups according to the procedure applied as those undergoing monopolar ablation (group 1, n=68) and those undergoing bipolar ablation (group 2, n=99). All patients were followed by electrocardiogram and 24-h Holter monitoring. Echocardiography was performed before discharge, at three and 12 months postoperatively, and annually thereafter. Left atrial volume index, left atrial diameter, and left ventricular ejection fraction were recorded. Results: There was no significant correlation between the procedure applied and hypertension, hyperlipidemia, diabetes mellitus, chronic obstructive pulmonary disease, history of the cerebrovascular events (p>0.05). The mean preoperative left atrial diameter decreased from 5.3 +/- 0.5 cm to 4.9 +/- 0.5 cm postoperatively in all patients (p=0.0001). The mean preoperative left atrial volume index decreased from 53.8 +/- 0.4 mL/m(2) t o 43.7 +/- 6.2 mL/m(2) in t he postoperative period (p=0.0001). During follow-up, 61.8% (n=42) of the patients in group 1 and 62.6% (n=62) of the patients in group 2 remained in sinus rhythm. One patient (1.5%) in group 1 and two patients (2.0%) in group 2 developed early postoperative cerebrovascular accident. Conclusion: Monopolar and bipolar ablation methods are safe and effective methods to ensure long-term sinus rhythm. Both procedures do not increase the morbidity risk with very low thromboembolic complication rates.
Keywords: Radiofrequency ablation; atrial fibrillation; monopolar ablation; bipolar ablation; SURGICAL-TREATMENT; PREDICTORS; SURGERY; IMPACT